Reutilización de aguas domiciliarias tratadas para el riego forestal - Tesón, Natalia (2019)
The reuse of municipal treated water for irrigation is an alternative to the discharge on surface waters that generate a sustained addition of nutrient and water for the trees. The objectives of this study are to evaluate reduction of the addition of nitrogen and phosphorus to the Salto Grande reservoir and to evaluate the effect on the growth of a Eucalyptus grandis W. Hill ex Maiden plantation. On the first 36 months, the total of wastewater reuse was 144.320 m3 and the increase of growth on irrigated plots was 35 %. Some changes in EC and SAR were detected, but they didn’t affect the trees. These preliminary results indicate that the reuse of wastewater for irrigation is an interesting alternative to the direct discharge.